AsiaSim 2013 13th International Conference on Systems Simulation, Singapore, November 6-8, 2013. Proceedings - Tan, Gary.; Yeo, Gee Kin.; Turner, Stephen John.; Teo, Yong Meng.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 13th International Conference on Systems Simulation, Asia Simulation 2013, held in Singapore, in November 2013. The 45 revised full papers presented together with 18 short papers were carefully reviewed and selected from numerous submissions. The papers address issues such as agent based simulation, scheduling algorithms, simulation methods and tools, simulation and visualization, modeling methodology, simulation in science and engineering, high performance computing and simulation and parallel and distributed simulation.
Agent based simulation -- Scheduling algorithms -- Simulation methods and tools -- Simulation and visualization -- Modeling methodology -- Simulation in science and engineering -- High performance computing and simulation -- Parallel and distributed simulation.
Keywords: Computer science; Computer network architectures; Computer system performance; Computer software; Computer simulation; Computer Science; Simulation and Modeling; Models and Principles; Algorithm Analysis and Problem Complexity; System Performance and Evaluation; Computer Systems Organization and Communication Networks